Synthesis and physicochemical properties of new triple lutetium tellurites - Toibek, A.; Rustembekov, K. (Journal of Chemical Technology and Metallurgy, 2025)
New triple lutetium tellurites LuMeFeTeO6 (Me - Sr, Ba) are synthesized using ceramic technology from oxides Lu2O3, TeO2, Fe2O3, carbonates SrCO3 and BaCO3. Using X - ray phase analysis, we confirmed the individuality, and determined the types of syngony, unit cell parameters, X - ray and pycnometric densities of compounds. It has been confirmed that tellurites crystallize in the tetragonal system with a distorted perovskite structural type. Using dynamic calorimetry in the temperature range 298.15 - 673 K, we studied the isobaric heat capacities of tellurites and derived equations for the Cp(T) dependence. The standard heat capacity of new tellurites has been determined, establishing a fundamental constant. We have calculated temperature dependences of the thermodynamic functions S0 (T), H0 (T) - H0 (298.15), Фхх (Т). The study results are significant for inorganic and physical chemistry of oxide materials, as well as inorganic materials science. They can be utilized for inclusion in reference books and thermodynamic data banks.
Keywords: lutetium; ternary tellurites; X - ray phase analysis; heat capacity; thermodynamic functions